Features of the intestinal microbiota in children with intestinal parasitosis - O. V. Kovaleva; L. A. Lityaeva (Детские инфекции (Москва))
The aim of the research is to study the features of the intestinal microbiota in children with parasitic invasions.Clinical and microbiological examination of 40 children aged from 9 months to 1 0 years with functional disorders of the intestine was carried out, in 20 of whom intestinal parasitoses were detected (15 of them — ascariasis, 5 — intestinal lambliosis) — the main group. The comparison group consisted of 20 other children with functional disorders of the intestine without intestinal parasitosis.All children underwent: assessment of the course of the ante-neonatal periods, the nature of feeding and clinical symptoms of intestinal parasitosis; triple study of feces for eggs of worms and protozoa in the enrichment environment of Turdyev, coprocytogram, biochemical analysis of feces, ultrasound of internal organs. To identify the quantitative content of the main groups of normobiota, species composition and spectrum of opportunistic bacteria and viruses, the method of gas chromatography-mass spectrometry of intestinal microbial markers was used.It was found that in children with intestinal parasitosis, already at the prenatal stage of the formation of the intestinal microbiota, risk factors were recorded that negatively affect the composition of the forming microbiota, associated with functional disorders of the digestive tract from the first days of life.The degree of deficiency of normobiota, as well as the spectrum of opportunistic bacteria in children with parasitic invasions, was greater: 14 types of bacteria in combination with herpes viruses versus 9 in the comparison group. Association Clostridium spp. — Herpes virus against the background of a deficiency of bifidobacteria and lactobacilli acts as a dominant association in the relationship with intestinal parasitosis.